Trans fats alternatives - Kodali, Dharma R., 1951-; List, Gary R. (AOCS Press, 2005)
Responding to government regulations that require declaration of the amount of trans fat present in foods, this book provides cutting-edge research and insights into a major industry issue. With contributions from major fats and oils suppliers, including Aarhus, ADM, Bunge, Cargill, Loders Croklaan, and Premium Vegetable Oils, the book covers the new regulations in detail, includes methods to analyze for trans fat, explores consumer reaction to trans fat labeling, discusses the nutrition facts, and supplies approaches to trans fat replacement/reformulation. It's an indispensable guide for everyone who is interested in trans fats.